Investigating the variability of Atlantic water inflow to the southwestern Barents Sea through Bjørnøyrenna during the Late Glacial and Holocene based on benthic foraminifera and sediment properties. - Tysnes, Anders (UiT Norges arktiske universitet, 2017)
This study is a part of the Barents Sea drill cuttings research initiative (BARCUT), investigating the inflow of Atlantic water to the southwestern Barents Sea during the Late Glacial and Holocene as well as providing data for future references. Five cores from the southwestern Barents Sea were used to investigate the inflow of Atlantic water to the southwestern Barents Sea through Bjørnøyrenna. The main method used is analyzing benthic foraminifera and the faunal composition, but total organic carbon (TOC), sortable silt mean grain size and grain size distribution are used as supporting data. The samples were sieved using mesh sizes of 1mm, 100mµ and 63mµ, but only the 100mµ-1mm fraction was used for the foraminiferal analysis. Samples from the top and bottom of the cores were sent to 14C dating to establish a timeframe. For the purpose of this thesis, four time intervals are selected for investigation, representing the Late Glacial (15 500-14 900yr BP), early Holocene (10 900-7300yr BP), mid Holocene (7300-2500yr BP) and late Holocene (2500-400yr BP). Signs of inflowing Atlantic water are first observed in the Late Glacial. However, it is possible that the core covering this time is partly reworked and thus care should be taken when interpreting the core. Atlantic water is present in the southwestern Barents Sea during the Holocene with varying inflowing strength and influence. The general warming and higher current strength throughout the early Holocene is due to increased inflow of Atlantic water. The currents calms and the Atlantic water flowing in to Bjørnøyrenna are cooler during the mid Holocene compared to the early Holocene. In the beginning of the late Holocene, a marginal ice zone (MIZ) is likely present in the studied area and a more vigorous environment occurs. During the late Holocene, the vigorous environment calms and by the end of the period only a weak current flows over the area, possibly influenced by a seasonal sea ice cover.